GAMBARAN HARGA DIRI PADA PASIEN YANG DILAKUKAN HISTEREKTOMI - Ni Putu Widari Triana, Ni Putu Widari Triana (D3 Kebidanan, 2012)
Self-esteem is about achieving self-study by analyzing how far self-ideal behavior according to low in the patient who performed a hysterectomy and is one of the problems that occur in patients who underwent hysterectomy. This is evident in the behavior exhibited by the patient is not willing to hang out, withdrew, did not want to know, male friends, and do not want to get married because he felt he was useless, feel useless as a wife, no self-confidence, feelings of inadequacy, guilt , easily offended. The purpose of this study was to identify about self-esteem in patients who underwent hysterectomy at the Hospital of Adi Husada Undaan Wetan Surabaya. The study design used is descriptive, the determination of samples with a total sampling method. Samples taken is a whole element to be studied ie 20 respondents. Collecting data using questionnaires. The data collected was processed manually and presented in tabular form. The results of the calculation results obtained from 20 respondents were 11 respondents (55%) had High Self-Esteem. 9 respondents (45%) had Low Self-Esteem. And it can be concluded that self-esteem in patients who underwent hysterectomy Adi Husada Hospital Undaan Wetan Surabaya have High Self-Esteem.Key words: Self-esteem, Action hysterectomy.